Soluções da eletrodinâmica generalizada em espaços-tempo curvos - Frizo, Diego Augusto (2019)
This work aims to investigate the generalized electrodynamics in curved space-time. From the Schwarzschild and Reissner-Nordström solutions for the Einstein equations with spherical symmetry and with temporal independence, it is desired to find solutions that take into account the generalized electrodynamics. For this, we want to find an expression for the electric field of generalized electrodynamics in the flat space-time and then use this electric field to find the components of the metric of the curved space-time. Finally, an analysis will be made of the results obtained such as the behavior of the horizons of events, the deviation of the trajectory of a ray of light and the temporal delay of a ray of light.